2015
DOI: 10.1071/ma15040
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired Clostridium difficile infection and Australian food animals

Abstract: Clostridium difficile is an anaerobic Gram positive spore-forming bacterium, the leading cause of infectious diarrhoea (C. difficile infection; CDI) in hospitalised humans. The assumption that CDI is primarily a hospital-acquired infection is being questioned. Community-acquired CDI (CA-CDI) is increasing1 particularly in groups previously considered at low risk2,3. In Australia, CA-CDI rates doubled during 2011 and increased by 24% between 2011 and 20124. Two potentially high-risk practices in Australian food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…difficile spores in the environment. These include curtailing the use of late-generation cephalosporins, immunization, environmental cleaning (e.g., sporicidal treatment of effluent) and discontinuing the practice of slaughtering neonatal calves (37, 50).…”
Section: Discussionmentioning
confidence: 99%
“…difficile spores in the environment. These include curtailing the use of late-generation cephalosporins, immunization, environmental cleaning (e.g., sporicidal treatment of effluent) and discontinuing the practice of slaughtering neonatal calves (37, 50).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that RT014 has established significant reservoirs in both human and porcine populations in Australia (Foster et al, 2014; Knight et al, 2014, 2015b; Collins et al, in press). These findings, together with a notable increase in CA-CDI in Australia, particularly in populations not considered to be at risk of CDI, have fuelled speculation that zoonotic transmission is a potential source of human infection (Slimings et al, 2014; Squire et al, 2015; Bloomfield and Riley, 2016). Using WGS and high-resolution core genome phylogenetics we describe for the first time the evolutionary relationships and extent of genetic overlap between strains of RT014 sourced from human and pigs in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Within Australia, two livestock/agricultural practices have been identified which could present significant risk for CA-CDI: (i) slaughtering of neonatal animals destined for human consumption, and (ii) the recycling of effluent to agriculture and compost manufacture with dissemination of contaminated vegetables and compost in the community setting (Squire and Riley, 2013; Squire et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals acquiring disease in the community setting do not have the classic risk factors for CDI acquisition and are generally young and healthy, without contact with hospital- ized patients and often without prior antimicrobial exposure (173)(174)(175). Notably, the genotypes of C. difficile strains acquired in the community differ from those of predominant hospital strains.…”
Section: Animal Reservoirs and Zoonotic Potentialmentioning
confidence: 99%